Pengaruh Pemberian Pupuk Organik dan Konsentrasi Pupuk Daun Terhadap Pertumbuhan dan Hasil Tanaman Selada Merah (Lactuca sativa L.) - KURNI, WASIH AL; FIRNIA, DEWI; ROMDHONAH, YAYU; ROHMAWATI, IMAS (Universitas Wahid Hasyim, 2024)
This research aimed to determine the effect of applying organic fertilizer and foliar fertilizer concentration on the growth and yield of red lettuce plants (Lactuca sativa L.). This research used a factorial randomized block design with 2 treatment factors using 2 levels and 4 levels in 3 replications. The first factor was organic fertilizer (coffee grounds and cow biourine) and the second factor was foliar fertilizer (Gandasil D). The result of the research showed that the application of organic fertilizer (coffee grounds and cow biourine) was able to have a real influence on the height of red lettuce plants at 1 – 4 WAP, the number of leaves of red lettuce plants at 2 and 3 WAP, the length of the roots of red lettuce plants, the wet weight of the roots of red lettuce plants, and wet weight of red lettuce plants canopy. Providing foliar fertilizer (Gandasil D) was able to have a real influence on the height of red lettuce plants 3 and 4 WAP, the number of leaves of red lettuce plants at 3 and 4 WAP, the length of the roots of red lettuce plants, and the wet weight of the crown of red lettuce plants. The interaction between organic fertilizer (coffee grounds and cow biourine) and foliar fertilizer (Gandasil D) was able to have a real influence on the height of red lettuce plants at 4 WAP, the number of leaves of red lettuce plants at 1 and 2 WAP, root length of red lettuce plants, and wet weight red lettuce plant header.